The most common dermatological manifestations of inflammatory bowel diseases - Hop, Izabela; Kołodziejczyk, Kacper; Branewska, Justyna; Ostrowska, Barbara; Olszanicka, Anna; Niemiec, Rafał; Galas, Adam; Matysek, Mikołaj; Maciąg, Anna; Imioło, Jan (Journal of Education, Health and Sport, 2023)
Inflammatory bowel diseases are increasingly common problem in clinical practice. This condition is caused by both the growing morbidity and more accurate and widely available diagnostic methods, affecting the rising recognition. It is worth remembering, that clinical presentation of inflammatory bowel disease is not limited to gastrointestinal tract. Dermatological symptoms are an important part in the diagnosis of inflammatory bowel diseases, because they can occur as the first manifestation of the beginning of the disease process, as well as be a prognostic factor for the occurrence of exacerbations of the disease. This is an invaluable source of information on the patient's clinical condition, affecting the effectiveness of his treatment in the early stages of the disease, and allowing more efficient control of its course. This has an enormous impact on the prognosis and comfort of patients' lives. In the following article, available medical studies on extraintestinal skin manifestations, clinical presentation and treatment options have been reviewed.